2021
DOI: 10.3171/case21308
|View full text |Cite
|
Sign up to set email alerts
|

Gout in the thoracic spine causing acute paraplegia: illustrative case

Abstract: BACKGROUND Although spinal involvement by gout is not uncommon, spinal gout leading to symptomatic spinal cord compression in the thoracic spine is very rare and poses a diagnostic challenge by mimicking symptoms of more common diagnoses such as epidural abscess and malignancy. An even more unique presentation is spinal gout causing thoracic cord compression leading to acute paraplegia. OBSERVATIONS The authors present an illustrative case of a 35-year-old man with thoracic spinal compression by tophaceous g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Современные подходы к хирургическому лечению подагрических спондилоартритов заключаются в выполнении декомпрессивной ламинэктомии с одновременной ревизией позвоночного канала и удалением параартикулярных и эпидуральных тофусов [32,33,34,35]. При наличии вертеброгенной нестабильности операция дополнялась транспедикулярной стабилизацией [13,15,17].…”
Section: характеристика работ включенных в систематический обзорunclassified
See 1 more Smart Citation
“…Современные подходы к хирургическому лечению подагрических спондилоартритов заключаются в выполнении декомпрессивной ламинэктомии с одновременной ревизией позвоночного канала и удалением параартикулярных и эпидуральных тофусов [32,33,34,35]. При наличии вертеброгенной нестабильности операция дополнялась транспедикулярной стабилизацией [13,15,17].…”
Section: характеристика работ включенных в систематический обзорunclassified
“…В свою очередь тактика применения антибактерильной терапии, по данным литературы, базируется на эмпирическом подходе ввиду крайне низкой частоты верификации возбудителя, препаратами выбора являются трициклические гликопептиды (ванкомицин) и цефалоспорины 3-4-го поколения [6,28,34]. Необходимо отметить, что в отличие от данных литературы в исследуемой нами клинической серии бактериологическое исследование операционного послеоперационного материала позволило выявить различные штаммы золотистого и эпидермального стафилококка (в том числе 3 случая нозокомиальной инфекции: MRSA, MRSE) и назначить этиотропную антибактериальную терапию с учетом лекарственной чувствительности возбудителей.…”
Section: характеристика работ включенных в систематический обзорunclassified
“…Despite traditional beliefs that spinal gout is rare, recent studies show it is more prevalent than reported because of underdiagnosis [ 3 ]. Nevertheless, such presentation in a patient who was never diagnosed with gout or hyperuricemia is rare [ 4 ]. This causes diagnostic challenges and potential treatment delays.…”
Section: Introductionmentioning
confidence: 99%